2018
DOI: 10.1002/aic.16396
|View full text |Cite
|
Sign up to set email alerts
|

RNAseq‐based transcriptome assembly of Clostridium acetobutylicum for functional genome annotation and discovery

Abstract: Accurate genome annotations are essential in modern biology and biotechnology, yet they are still largely based on genome sequencing and comparative analyses. We show that the Clostridium acetobutylicum genome annotation can be markedly improved by integrating bioinformatic predictions with RNA sequencing (RNAseq) data. Samples were acquired under butanol, butyrate, and unstressed treatments across various growth conditions. Analysis of an initial assembly revealed errors due to background signals and limitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
(149 reference statements)
0
4
0
Order By: Relevance
“…To establish the abundance of raiA motif RNAs relative to other transcripts, we analyzed previously published C. acetobutylicum whole-transcriptome RNAseq data ( 49 ). Transcriptomics data were derived from cells collected 75 min past an OD 600 measurement of 1 and therefore represent cells at or near stationary phase.…”
Section: Resultsmentioning
confidence: 99%
“…To establish the abundance of raiA motif RNAs relative to other transcripts, we analyzed previously published C. acetobutylicum whole-transcriptome RNAseq data ( 49 ). Transcriptomics data were derived from cells collected 75 min past an OD 600 measurement of 1 and therefore represent cells at or near stationary phase.…”
Section: Resultsmentioning
confidence: 99%
“…This is comparable to the proposed regulation by SolB in C. acetobutylicum ( Jones et al, 2018 ). Furthermore, some reads antisense to the sol operon of C. acetobutylicum , consisting of adhE , ctfA , and ctfB , were identified by transcriptomics ( Ralston and Papoutsakis, 2018 ), but the transcript and its regulatory role were not further investigated. In addition, the authors mention over 400 possible antisense interactions for other metabolic pathways ( Ralston and Papoutsakis, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some reads antisense to the sol operon of C. acetobutylicum , consisting of adhE , ctfA , and ctfB , were identified by transcriptomics ( Ralston and Papoutsakis, 2018 ), but the transcript and its regulatory role were not further investigated. In addition, the authors mention over 400 possible antisense interactions for other metabolic pathways ( Ralston and Papoutsakis, 2018 ). This was also found in the transcriptomic data of C. saccharoperbutylacetonicum , e.g., transcripts antisense of the butyryl-CoA synthesis operon (Cspa_c04330 to Cspa_c04370) or the pta-ack operon (Cspa_c13010 and Cspa_c13020) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly 3 -UTR confer stability to the mRNA (Zhao et al, 2018). Although, there are very limited studies related to 3 -UTR regions in Clostridium, the presence of transcripts with long 3 -UTR is confirmed in Clostridium (Ralston and Papoutsakis, 2018). Although several RNAseq studies were reported in the Clostridium, only few studies show the data related to regulation of mRNA based on 5 -and 3 -UTRs, leaderless transcripts and non-coding RNA (Soutourina et al, 2013;Wilson et al, 2013;Sedlar et al, 2018).…”
Section: Synthetic Srna and Untranslated Region Engineering As Potentmentioning
confidence: 99%